Kebijakan Hukum Pidana Perlindungan Korban Perkawinan Terhadap Anak Di Bawah Umur (Studi Kasus : Perkawinan Pujiono Cahyo Widianto Dengan Lutviana Ulfah) - Fadilah Nursirnayati, Nyoman Serikat Putra Jaya, Eko Soponyono (Diponegoro Law Journal, 2012)
One example of the phenomenon of child marriages were quite attracted various groups is a marriage performed by Pujiono Cahyo Widianto familiarly called Sheikh Praise then be shortened to PCW 43 (forty three years old) with Lutviana Ulfah 12 (twelve years old). This study aims to determine how the policy of protection of victims of criminal law marriage against minors present and future. The approach used in this study were analyzed using descriptive normative analytical.